(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Equal-channel angular pressing (ECAP) is a severe plastic deformation (SPD) method, which used to produce ultra fine-grained (UFG) material . The conventional way to develop press-formed metallic components requires a burden some trial-and-error process for setting-up the technology, whose success depends largely on the operator’s skill and experience [6,7]. The finite element (FE) simulations of ECAP process help the manufacturing engineer to design a forming process by shifting the costly press-shop try-outs to the computer-aided design environment. Numerical simulations of a manufacturing process, such as ECAP, have been introduced, in order to avoid the trial-and-error procedure and to shorten the development phases when tight time-tomarket is demanded. The main aim of the investigation presented in this paper is to develop a numerical model that would be able to successfully simulate the ECAP pressing. The finite-element method was used for die and billetbehavior predictions during the process. The as-received alloy used in this study was the 6082 commercial Al-Mg-Si alloy. High strength and high ductility phenomenon which recently was found in materials after ECAP were reached with the route C technique up to eight passes with a high length to diameter ratio i.e. 15-16. The induced anisotropy of specimens after ECAP was monitored.